Optical and Photoelectrical Properties of Single Sapphire Crystal After Irradiation with Silicon Ions; 8th International Conference on Modification of materials with Particles Beams and Plasma Flows, Tomsk, September 10-15, 2006 - Kabyshev A. V. Alexander Vasilievich (2006, 2006)
Title screen